"A new horizon?": evaluation of an integrated Substance Use Treatment Programme (SUTP) for mentally disordered offenders. Issue 2 (18th May 2015) - Miles, Helen
Abstract : Purpose: – The treatment of substance use amongst mentally disordered offenders (MDOs) remains a challenge for secure forensic mental health services. The purpose of this paper is to present an integrated three-stage substance use treatment programme (SUTP) for male and female MDO's in medium security. Design/methodology/approach: – In total, 45 (72.6 per cent) MDO's were referred (39 males/6 females). Standardised outcome measures were administered pre-SUTP, post-SUTP and at one year follow-up. Abstinence rates and location was determined via case notes at three year follow-up. Findings: – All MDO's had a past history of substance use, approximately three-quarters reporting problematic use prior to admission. Over half completed all three SUTP stages, less than 5 per cent dropping out during active treatment. The SUTP supported abstinence throughout the one year follow-up period and significantly improved MDO's adaptive beliefs about substances and craving by one year follow-up amongst attendees. At three years, most MDO's were in the community and almost three-quarters were abstinent. There was no significant difference in abstinent rates between community and hospital. There was a non-significant trend suggesting SUTP attendance supported abstinence. Both male and female participants appear to have benefited from treatment and satisfaction was high, reflecting the specific aims and objectives of treatment. Research limitations/implications: – The small non-randomised sample from one area limits the generalisability of findings and statistical power. Originality/value: – Findings indicate further support for the limited evidence base that small but clinically meaningful and maintained changes to problematic substance use are possible following integrated substance use treatment for male and female MDO's.